The Vallejo Gospel - Sánchez Lihón, Danilo (Espergesia, 2018)
The purpose of this article is to stimulate the solidarity of human beings based on the poetic work of César Vallejo who, due to his profound humanism, becomes a kind of universal gospel of love to which all humanity must follow. This proposal of religion is based on the España, aparta de mí este cáliz collection of poems and especially on the poem “Masa” in whose verses the proposal of the union of human beings: men, women and children are implicit; the idea of humanity as an indivisible whole. Through the five chapters, explain the meaning of this gospel and how to get there. The condition that proposes to arrive, we find it summarized in a single word: all. This word refers to total love, to that love for neighbor that leads us to solidarity, which we must use as a shield. He concludes by affirming that solidarity is the only path that leads to the greatness of human, legitimate and invincible man to claim for all that we have suffered.